The SPP-Payment Information System at MA Babussalam Payaraman Using Rapid Application Development (RAD) - Hifzir Ridho; Fenando; Catur Eri Gunawan (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The development of information technology has had a significant impact on various sectors, including the education sector. MA Babussalam Payaraman, as an Islamic educational institution, recognizes the importance of integrating technology to improve management efficiency. One of the crucial aspects in madrasah financial management is the tuition fee payment system (Sumbangan Pembinaan Pendidikan, SPP). This study aims to design and implement an efficient SPP Payment Information System at MA Babussalam Payaraman. The development method used is RAD (Rapid Application Development) to accelerate the system development process. During the research phase, an in-depth understanding of the madrasah's needs and the SPP payment process was conducted. Next, a system prototype design was created to be adaptable to user needs. The RAD implementation process allows for iterative development and active participation from users, ensuring the system meets the actual needs of the madrasah. This study resulted in an SPP Payment Information System that can be used by the Madrasah Aliyah Babussalam to facilitate the SPP payment process and report generation.